Psychosocial Safety Climate And Burnout Among Malaysian Research University Academicians: The Mediating Roles Of Work Engagement And Job Demands - Teoh, Kok Ban (2020)
Nowadays, the burnout prevalence among academicians is inclining in Malaysian Research Universities. Moreover, a high level of job demands and a low level of job resources have lead academicians to experience more burnout. Hence, it signals the need to examine the predictors of burnout level among Malaysian research university academicians. Based on Conservation of Resources Theory, this study builds a research framework to govern the investigation of psychosocial safety climate, challenge demands, hindrance demands and work engagement as the predictors of burnout level with work engagement, challenge demands and hindrance demands as the mediating variables. Online questionnaire was sent to all academicians working in Malaysian Research Universities, namely Universiti Malaya, Universiti Kebangsaan Malaysia, Universiti Sains Malaysia, Universiti Putra Malaysia and Universiti Teknologi Malaysia. A total of 686 academicians from Malaysian research universities participated in the research. The data collected were analysed using partial least squares structural equation modeling. Based on the analysis, the study indicated that psychosocial safety climate and work engagement have a significant negative relationship with burnout while challenge demands and hindrance demands have a significant positive relationship with burnout. The results also exhibited that psychosocial safety climate and challenge demands have a significant positive relationship with work engagement whereas hindrance demands has a significant negative relationship with work engagement.